2018
DOI: 10.1017/s0014479718000133
|View full text |Cite
|
Sign up to set email alerts
|

Agro-Physiological Characterization of Durum Wheat Genotypes Under Drought Conditions

Abstract: SUMMARYKnowledge of agro-physiological traits associated with drought tolerance would be useful for developing breeding materials for drought-prone environments. This study was conducted (i) to estimate genetic variability among 25 durum wheat genotypes in response to drought based on grain yield and 15 agro-physiological traits in single and multi-year trials; and (ii) to compare genotypes on the basis of multiple investigated traits using genotype by trait (GT) biplot technique and then recommend possible se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 33 publications
(42 reference statements)
1
19
0
Order By: Relevance
“…Based on across-year analyses, HT, PH, and TGW are the most promising traits for indirect selection. Similar data were obtained by Mohammadi et al (2018) for 25 durum wheat breeding genotypes under drought conditions, and by González-Ribot et al (2017) for a durum wheat collection. The negative relationship between GY and PC and GC might be due to opposite pleiotropic gene effects, caused by the major bio-energetic requirements for synthesis of protein and then carbohydrate (Blanco et al, 2006).…”
Section: Discussionsupporting
confidence: 75%
“…Based on across-year analyses, HT, PH, and TGW are the most promising traits for indirect selection. Similar data were obtained by Mohammadi et al (2018) for 25 durum wheat breeding genotypes under drought conditions, and by González-Ribot et al (2017) for a durum wheat collection. The negative relationship between GY and PC and GC might be due to opposite pleiotropic gene effects, caused by the major bio-energetic requirements for synthesis of protein and then carbohydrate (Blanco et al, 2006).…”
Section: Discussionsupporting
confidence: 75%
“…potentially be a subject of many environmental constraints which can have adverse effects on its yield and yield stability (Mohammadi et al, 2018). Over the past years, durum wheat production has been fluctuating significantly due to climate change and drought in particular (Boussakouran et al, 2019).…”
Section: ____________________________________________________________ ___________________________________________________________________mentioning
confidence: 99%
“…Drought acts on the PSII reaction centers of the photosynthetic system and the stomata (Paknejad et al, 2007), thus inducing reductions in grain yields (Jedmowski et al, 2013). Mohammadi et al (2018) argue that fluorescence measurements can help improve the overall agricultural productivity and grain yield of durum wheat under fluctuating climatic conditions. Direct and indirect changes in fluorescence induction kinetics following abiotic stress have been studied in a number of crops (Baker et al, 2001).…”
Section: ____________________________________________________________ ___________________________________________________________________mentioning
confidence: 99%
“…In two years of research by Đurić et al (2017) on the influence of agrometeorological conditions, it was found that in the vegetative season with more precipitation than 176 mm, and average temperatures lower by 3.1 °C, the TGW had higher values. Mohammadi et al (2019) concluded that the characteristics of genotypes of wheat have a great influence than years as a factor. According to their research, the results show that efficiency of photosystem II and thousand-kernel weight were positively associated with grain yield, while heading date, plant height and canopy temperature were negatively associated with grain yield under drought conditions.…”
Section: Discussionmentioning
confidence: 99%